BRCA1 cooperates with NUFIP and P-TEFb to activate transcription by RNA polymerase II. - Cabart, P; Chew, H; Murphy, S (2004)
The tumor suppressor gene product BRCA1 is a component of the RNA polymerase II (pol II) holoenzyme that is involved, through binding to various regulatory proteins, in either activation or repression of transcription. Using a yeast two-hybrid screen, we have identified a human zinc-finger-containing protein NUFIP that interacts with BRCA1. The ubiquitous, stably expressed, nuclear protein NUFIP specifically stimulates activator-independent pol II transcription in vitro and in vivo. Immunodepletion of the endogenous NUFIP causes a marked decrease of pol II transcription, which is then shown to be restored by stable complex of ectopically produced NUFIP and associated factors. NUFIP not only interacts with BRCA1 but also associates with the positive elongation factor P-TEFb through interaction with the regulatory Cyclin T1 subunit. Cyclin T1 is required for BRCA1- and NUFIP-dependent synergistic activation of pol II transcription in 293 cells. Mutation of the zinc-finger domain abolishes the NUFIP-mediated transcriptional activation. We show that NUFIP is associated with preinitiation complexes, open transcription complexes, and elongation complexes. In addition, NUFIP facilitates ATP-dependent dissociation of hyperphosphorylated pol II from open transcription complexes in vitro.